Development of SMAN 1 Ciasem Ascenter of Education in the Staged Guidance Service Program (Plb2) in Ciasem District - Aris Priatna; Babang Robandi; Eviana Hikamudin (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
Improving the quality of education through independence and own initiative in the management of existing resources in schools is the main characteristic of implementing SBM. The difficulty of implementing the curriculum as a whole is one of the problems faced by educational institutions in the regions. The low effectiveness of teaching and learning, the minimal and limited supporting facilities and infrastructure for teaching and learning that are available and the low competence of teachers are the main causes of the low quality of students. To overcome the above problems, it is necessary to handle integrated guidance services that involve components of education providers at one level or between levels. The guidance service program is held within the Multilevel Guidance Service Program (PLB2). The existence of a communication forum for subject teachers at the sub-district level in the form of this communication forum is expected to occur in interaction between fellow subject teachers so that weaknesses, deficiencies and potentials can be identified.